2020
DOI: 10.4236/gep.2020.88001
|View full text |Cite
|
Sign up to set email alerts
|

Fine Particulate Matter and Heavy Metals Pollution Status in Ambient Air of Some Selected Industrial Sites in Northern Nigeria

Abstract: Fine particulate matter and eight heavy metals (Ni, Co, Cu, Pb, Cd, Cr, Mn, and Zn) concentrations were determined in air samples collected from three industrial sites in northern Nigeria using a Handheld Portable Particle Counter for PM 2.5 and PM 10 with model number CW-HAT 200 and a High Volume Respirable Dust Sampler (APM 460 NL) in conjunction with an Atomic Absorption Spectrophotometer (Serial No. AA0904M046) Flame Test. The results of the fine particulates ranged from 11.0 -46.0 µg•m −3 for PM 2.5 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Concentrations of cadmium, nickel, and manganese greatly exceeded WHO-recommended limits, indicating vehicular traffic and waste incineration as sources. Further studies by Ayua et al (2020) reported heavy metals in resp irable dust and particulate matter around industrial sites in Kano, Kaduna, and Jos. They reported concentrations of cadmium, nickel, and lead that exceeded WHO standards in some areas, implicating industrial activities as a significant contributor to air pollution.…”
Section: Ogbeide O; Henry Bmentioning
confidence: 92%
See 1 more Smart Citation
“…Concentrations of cadmium, nickel, and manganese greatly exceeded WHO-recommended limits, indicating vehicular traffic and waste incineration as sources. Further studies by Ayua et al (2020) reported heavy metals in resp irable dust and particulate matter around industrial sites in Kano, Kaduna, and Jos. They reported concentrations of cadmium, nickel, and lead that exceeded WHO standards in some areas, implicating industrial activities as a significant contributor to air pollution.…”
Section: Ogbeide O; Henry Bmentioning
confidence: 92%
“…Heavy metals have been detected in the atmosphere, according to studies. Ayua et al (2020), measured the concentrations of eight heavy metals (Ni, Co, Cu, Pb, Cd, Cr, Mn, and Zn) in air samples taken from three industrial locations in Northern Nigeria: Kano, Kaduna, and Jos. The data was gathered between September 2018 and August 2019.…”
Section: Ogbeide O; Henry Bmentioning
confidence: 99%
“…Chronic bronchitis, benign organic dust toxicity syndrome, hyperactive airway disease, chronic asthma, membrane irritation, and even worsening of COVID-19 symptoms have all been linked to fine particulate matter exposure [16][17][18]. To build successful abatement methods for lowering air pollution, it is critical to have knowledge of emission source data and an understanding of the meteorological conditions that affect air pollution [14,19].…”
Section: Introductionmentioning
confidence: 99%
“…When a person exceeds the prescribed limit for trace metals, that person may become toxic (acute, chronic, or subchronic), which may cause neurotoxicity, carcinogenicity, mitogenicity, or teratogenicity (Abro & Gomez-Aguilar, 2019;Dżugan, 2010;Silbergeld, 2003;Tchounwou et al, 2019). According to a recently published studies, among of the most common symptoms reported for humans who have been exposed to the toxic metals include vomiting, convulsions, paralysis, ataxia, gastrointestinal disorders, diarrhea, stomatitis, depression, and pneumonia (Ayenimo et al, 2010;Ayua et al, 2020;Bashir, 2018;Flora, 2014;Guérin et al, 2011;Onakpa et al, 2018;Rweyemamu & Nkansah, 2021;Singh et al, 2017;Shelar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%